Correlation Between Executive Function and Gratitude of International Acehnese College Student In Malaysia - Rahmah, Siti; Zuanny, Iyulen Febri; Hanifah, Rulia (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The research was conducted to look at correlation between executive function and gratitude of college students. The subjects used were the international Acehnese student in Malaysia. The subjects were chosen by stratifield random sampling techniques with quantitative research approaches. The instrument were The Executive Function Index (EFI) and Gratitude Questionnaire (GQ-6) based on Likert Scale. SPSS (Statistical Package for Social Science) was used to administer and manage the collected data. The data was analyzed using descriptive statistics (min and percentage) and inference statistics which were the Pearson corelation, ANOVA and Regression. The hypothesis stating that there was statistically significant corelation between Executive Function and Gratitude was accepted as (r= .631, p .01). based on the research, several implications and suggestions are given.